Prehistoric nests of Mud Dauber Wasps (Hymenoptera: Sphecidae) discovered in Transylvania, Romania - Alexandra Florina Popa; Valerii Kavruk; Corneliu Beldiman (Travaux du Muséum National d’Histoire Naturelle “Grigore Antipa”, 2022)
Fragments of mud dauber wasp’s nests dating from the Bronze Age (Noua culture, about 1500–1200 BC) from a Romanian archaeological site are described. The present discovery represents, to our knowledge, the first reported fragments of mud dauber nests recuperated from an archaeological site in Romania and probably among the rare ones from Europe. The archaeological site called Zoltan-“Nisipărie” is placed in the Covasna County, south-eastern Transylvania. The five fragments belong to two nests made by Sceliphron sp. wasps genus and they were described in terms of general and detailed morphology and morphometry. Two nest fragments preserve in situ secondary cells, showing evidence of nest reoccupation by other insects. Another important aspect of this discovery is the opportunity to extract and analyse a whole secondary cell from the original nest fragment. Various impressions of vegetal material (grass, straws etc.) and a seed on the nest fragments’ surface were observed using microscopic techniques. The preserved pieces recovered from archaeological investigations provide important data regarding the local environmental conditions during the recent period of Bronze Age in an anthropized environment of the Noua culture.